Perancangan Kawasan Seni Budaya Betawi Dengan Arsitektur Neo Vernakular Di Kota Tangerang Selatan - Muhamad Sahrul; Harfa Iskandaria; Karya Subagya (MAESTRO, 2023)
The inhabitants of South Tangerang City have a culture that must be protected, and that culture is betawi. However, the general public is not aware of Betawi culture's existence. To advance and uphold Betawi culture, the Betawi Cultural Institute (LBB) of South Tangerang City organizes a Betawi cultural festival every year. In compliance with the South Tangerang City Regional Regulation regulating the preservation of Betawi culture, the design of the Betawi Cultural Arts Area strives to bring together all activities and events pertaining to Betawi culture. The use of neo vernacular architecture in this area is one way to introduce Betawi culture in terms of architecture. The building's design is modern while retaining elements of Betawi culture. The Betawi Cultural Arts Area is a destination for cultural tourism that aims to introduce and preserve Betawi culture in South Tangerang City.